To make a classic, use two. No sense of place by Joshua Meyrowitz, between Goffman and McLuhan - Serra, Marcello (Anuario ThinkEPI, 2024)
No sense of place, by Joshua Meyrowitz, is a classic of communication studies that has never been translated into Spanish. The work combines the thought of Marshall McLuhan with the dramaturgical conception of Erving Goffman, elaborating an original model for the analysis of the influence of the media on social behavior. Almost forty years after its publication, Meyrowitz’s perspective helps us to understand phenomena that are highly topical, such as the crisis of expert knowledge, the loss of leadership in politics or the redefinition of gender roles. This analytical longevity gives legitimacy to the ambition of considering the media as a fundamental variable for the study of society and its transformations.